Chemistry / Raymond Chang; Kenneth A Goldsby - Chang, RaymondAuthor
Designed for the two-semester general chemistry course, Chang's best-selling textbook continues to take a traditional approach and is often considered a student and teacher favorite. The book features a straightforward, clear writing style and proven problem-solving strategies. It continues the tradition of providing a firm foundation in chemical concepts and principles while presenting a broad range of topics in a clear, concise manner. The tradition of "Chemistry" has a new addition with co-author, Kenneth Goldsby from Florida State University, adding variations to the 11th edition. The organization of the chapter order has changed with nuclear chemistry moving up in the chapter order. There is a new problem type - Interpreting, Modeling, and Estimating - fully demonstrating what a real life chemist does on a daily basis. The authors have added over 340 new problems to the book. The new edition of "Chemistry" continues to strike a balance between theory and application by incorporating real examples and helping students visualize the three-dimensional atomic and molecular structures that are the basis of chemical activity. An integral part of the text is to develop students' problem-solving and critical thinking skills. The 11th edition continues to deliver the integration of tools designed to inspire both students and instructors. Effective technology is integrated throughout the book.